Lack of Visibility of Eco-Labels: A Study on Consumer Deception - Khadir, Fezeena; Singh, Ankita; Devi, Jyoti; Sharma, Kanica (International Journal of Psychosocial Rehabilitation, 2020)
This paper focuses on consumer deception and aims to understand the level of awareness of ecolabels amongst consumers, whether they fall prey to the deception of pseudo eco-claims and if so, what are the reasons for the persistence of this malpractice. It aims to answer the following questions, (1) why eco-labels are scarcely used and mostly go unnoticed while there is more awareness about regular labels, (2) how can consumers distinguish between eco-label and pseudo eco-claim, (3) is there a need to recreate the existing eco-labels which can represent an overall assessment of a product’s environmental burden over its entire life cycle. The main contributions of the paper are that it will help consumers from falling for the deceptive practices which only claim to offer eco-friendly products and it will also benefit the companies which actually stand up to their eco-claims but often get overshadowed by the existence of pseudo eco-claims. A questionnaire survey was conducted which targeted individuals from the Indian demographics who regularly purchase items from the market. The objectives of the survey were to understand the individual’s level of awareness about the eco-labels, if they could recognize ecolabels and regular labels and if they could distinguish between eco-labels and eco-claims. The systematic reviewing of earlier research literature revealed that there is a lack of consumer awareness and that there is a dire need for law enforcement. This paper highlights the fact that in spite of the existence of government accredited eco-labels and laws to stop these deceptive practices, it is still practiced. It was found that these labels mostly go unnoticed or are absent from the product and the explicit visibility of pseudoeco-claims leads to the consumers blindly accepting the authenticity of these products or getting skeptical about all eco-products/labels. In the absence of specific logos for each phase of eco-transitions, which various companies are currently going through, there arises the problem of ambiguity about what the term ‘sustainability’ stands for. The present study will contribute significantly to the existing body of knowledge in regard to creating awareness of existing pseudo eco-claims and bring about a new standard for eco-labeling. It will also benefit industries whose eco-claims are genuine.